Application of Life Cycle Assessment (LCA) in measuring the environmental impact of coal-fired power plant - A review - Mardi N.H.; Ean L.-W.; Chua K.-H.; Malek M.A. (EDP Sciences, 2023)
Coal-fired power is among the most significant electric generated in most developed countries. The environmental impact of coal-fired power plants is usually associated with air, water and waste pollution. Life cycle assessment (LCA) is a standard method used to evaluate the potential of environmental impacts of a product or process over its life cycle stages. This paper aims to review the application of LCA in evaluating the environmental impact of coal-fired power plant fields. The results were summarised in term of goal, scope, functional unit, system boundaries, impact assessment method and impact category. The Authors, published by EDP Sciences.